Islamic Religious Education Learning Strategies to Enhance Students' Literacy Enthusiasm in Elementary Schools - Muhammad Rizal; M. Nasri Hamang S; Muhammad Nur Maallah; Suredah Hamid (EDUJAVARE: International Journal of Educational Research, 2026)
This study addresses challenges in elementary students’ literacy enthusiasm in Islamic Religious Education (PAI), including low interest in religious reading, the continued use of lecture-and-memorization practices, and the lack of a structured literacy program. It aims to describe PAI learning strategies used to cultivate students’ literacy enthusiasm, identify supporting and inhibiting factors, and evaluate their effectiveness at SD Negeri 8 Tampaan, Enrekang Regency. Using a descriptive qualitative approach with theological-normative, pedagogical, psychological, and sociological perspectives, the researchers collected data through passive-participant observation, in-depth interviews with principals, PAI teachers, homeroom teachers, students, parents, and other stakeholders, as well as documentation studies. Data were analyzed using Miles and Huberman’s procedures, and validity was ensured through credibility, transferability, dependability, and confirmability. Findings show that PAI teachers implement four integrated strategies: contextual inquiry-based learning, digital platforms as a “living library” with digital tabayun, contextual text criticism through a “text–context–reflection” approach, and differentiated instruction producing creative literacy products. Support comes from school policy, teacher creativity, involvement of the school committee and parents, and innovative library management, though limitations remain in teachers’ critical digital literacy and declining deep-reading ability due to instant digital content. Overall, the strategies drive behavioral change and generate diverse, spiritually meaningful literacy outputs.